Factors Associated with Neuropathy Incidence based on 10 g Monofilament Examination in Type 2 Diabetes Mellitus Patients - Dewi, Ratna; Faizal, Kgs. M.; Hermain, Hermain (Genius Journal, 2025)
Introduction: Diabetic neuropathy is damage caused by excessive blood sugar levels. Neuropathy can be defined by certain signs or specific symptoms that are usually experienced by people with diabetes. Neuropathy causes nerve disorders resulting in pain or numbness, especially in the extremities. Objective: This study aims to determine the factors associated with the occurrence of neuropathy through 10 gr monofilament examination in Type 2 diabetes patients at Sejiran Setason Hospital, West Bangka in 2024. Method: This research design uses a cross-sectional approach to determine the relationship between the variables studied at a certain time. The population of this study was patients with type 2 diabetes mellitus at Sejiran Setason Hospital West Bangka from January to December in 2024. The number of research samples was 166 people. The collected data were then analyzed univariately and bivariately using the chi-square test at 95% dk (α=0.05). Result: The results of this study prove that there is a relationship between age (p-value = 0.013, POR = 3.820), duration of suffering (p-value = 0.006, POR = 3.290), and physical activity (p-value = 0.000, POR = 5.413) with the incidence of neuropathy at Sejiran Setason Regional Hospital, West Bangka in 2024. The most dominant factor in relation to the incidence of neuropathy is physical activity (POR = 5.413). Conclusion: The recommendation from this study is that Type 2 DM patients need to do physical activity for at least 30 minutes a day, 3-5 times a week, recognize and monitor body changes regularly and carry out routine screening examinations for diabetes mellitus risk factors to detect diabetes mellitus risk factors early.